Forex In The Eyes Of Shariah: A Qualitative Analysis In The Malaysian Context - Muhammad Nadzif Ramlan; Nurfarah Amira Mohd Zaini; Umi Aisyah Jamil; Nur Aliah Farhana Raof; Nurul Faiezi Zahar; Faidhi Hakim Mohd Nordin (USIM Press, 2024)
Journal of Fatwa Management and Research (JFatwa) Volume 28 No.3 Page (82-112)